Elaboração e implementação piloto de um portal para o apoio à cooperação científica e tecnológica e sua aplicação à área de tratamento de superfícies metálicas - Garcia, Leonardo Guimarães (2005)
The globalization and the Communication and Information Technologies (CIT´s) have been, respectively, increased the demand and facilitated the existence of cooperation associated to innovation, research and development (R&D). In Brazil colaborative actions in R&D, particularly among companies and universities, are limited due to cultural and historic reasons. By the other hand, despite the Internet to be a TIC recognized by its capacity to integrate people and institutions, the current portals also have mechanisms yet incipient for the stimulus to cooperation in R&D. This occurs in large and small technological areas like Metallic Surface Treatment (MST). The present work aims to promote the innovation by implement, in a pilot scale, an Internet portal, to act in the linkage among people and institutions that are responsible by the R&D in MST. The results indicated that portals like this give relevant contributions to the R&D´s sectorial processes facilitating the diagnosis and the strategic direction of collective actions to overcome problems related to innovation, besides the generation as of information and ideas for R&D as of synergy and trust in cooperation, allowing to the sector to take advantages of cooperation to improve its R&D.